DISTRIBUTION OF DIFFERENT FORMS OF NITROGEN IN BRACKISHWATER FISH-POND SOILS OF WEST BENGAL - Chattopadhyay, G N; Mandal, L N (Indian Journal of Fisheries, 2011)
Total nitrogen content of the soils from sixteen brackishwater ponds rangedfrom 220 to 420 ppm with an aveirage vclue of 330 ppm which was much lessthan what is generally found in freshwater pond soils. Available nitrogen levelwas also rather low ranging from 50.4 to 110.6 ppm with an averags value of89.9 ppm. NH4+form of nitrogen occurred in higher amount than the 'NO3- formwith average values of 16.8 and 8.9 ppm respectively. C:'N ratios of the soilsranged from 10.0 to 14.1 with an averagfc valu; of 12.5. The results emphas'zedthe need of application of nitrogen through fertilizers or manures for increasingtheir productivity.